Male and Female Physicians in Hospital Gynaecology Departments – Analysis of the Impact of “Feminisation” from the Viewpoint of Medical Directors - Riepen, T.; Möbus, V.; Kullmer, U.; Tinneberg, H. R.; Münstedt, K. (Geburtshilfe und Frauenheilkunde, 2013)
Introduction: At present the topic “feminisation” in medicine, in other words the increasing number of female staff members is under heavy discussion; however, there are only few data upon the basis of which a scientific discussion can be held. The question arises as to the possibility of problems arising therefrom for the specialty gynaecology and obstetrics. Methods: With the help of a questionnaire the directors of departments of gynaecology and obstetrics were questioned about the various aspects of the topic feminisation in gynaecology and obstetrics. Results: Among current applications the proportion of female applicants is estimated to be 84.2 %. Reasons given most frequently for the feminisation in the specialty include low income, loss of face of the medical profession and the poor career chances. Among the spontaneously mentioned reasons were the increasingly female dominated image of gynaecology and the working conditions in hospitals. Whereas the taking on of surgical duties and of directing functions was less markedly desired by women than by men, the questioned directors found that male and female staff members were equally motivated to take on duties outside of their working hours or to engage in research work. Discussion: Feminisation in medicine represents a challenge. It seems to be important to evaluate and investigate the motivation of staff members with regard to their wishes in professional life and thus to be able to offer an appropriate working environment based on the survey results.
Keywords: feminisation; gynaecology; obstetrics; career planning; motivation